Latent structure of a social anomie scale and factor invariance in peruvian students of both sexes - Caycho Caja, Aaron (2020)
The objective of this research was to find evidence of the latent structure of the Social Anomie Scale as well as to generate empirical support for the factor invariance hypothesis according to the sex of 301 Peruvian pre-university students. A confirmatory factor analysis of each model was carried out, it was found support to the internal consistency of the scale, and then the factorial invariance of the proposed Model 2020 was raised. The results indicate that the model of three underlying factors is not sustained in its internal consistency; alternatively, the model of two factors obtains empirical evidence in favor of its consistency and internal structure. As for the weak invariance, this is not justified by problems linked to the group of women. It is concluded that the Social Anomie Scale shows difficulties associated with the presence of the subscale of Pessimism and in the evaluation of female participants.